2015
DOI: 10.1109/tnano.2015.2425433
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement in Peak Detectivity and Operating Temperature of Strain-Coupled InAs/GaAs Quantum Dot Infrared Photodetectors by Rapid Thermal Annealing

Abstract: We report the effects of rapid thermal annealing on the optical, structural, and device properties of 30 layer straincoupled InAs/GaAs quantum dot infrared photodetectors. Stability in the photoluminescence peak is observed for annealing up to 800°C, which has not been previously reported. Cross-sectional transmission electron microscopy images show preservation of quantum dots is observed up to 800°C. Device with total capping thickness of 150 nm annealed at 750°C exhibit a fivefold enhancement in spectral in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Under the lowest measured incident light, power density achieves 8 × 10 − 5 mW cm − 2 , and the highest R , EQE, and D * are calculated to be 98.17 A W − 1 , 2.65 × 10 4 % and 1.62 × 10 15 cm Hz 1/2 W − 1 (Jones), respectively. Note that the extraordinarily high D * value of the present device (exceeding 10 15 cm Hz 1/2 W − 1 ) is among the record high reported for the perovskite photosensors so far, and it is even higher than that of devices based on single-crystalline silicon 56 , InGaAs 57 , GaAs 58 , CdTe 59 , and GaN 60 , demonstrating much superior quality of the 2D layered (PEA) 2 PbI 4 single-crystalline perovskite membrane material.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Under the lowest measured incident light, power density achieves 8 × 10 − 5 mW cm − 2 , and the highest R , EQE, and D * are calculated to be 98.17 A W − 1 , 2.65 × 10 4 % and 1.62 × 10 15 cm Hz 1/2 W − 1 (Jones), respectively. Note that the extraordinarily high D * value of the present device (exceeding 10 15 cm Hz 1/2 W − 1 ) is among the record high reported for the perovskite photosensors so far, and it is even higher than that of devices based on single-crystalline silicon 56 , InGaAs 57 , GaAs 58 , CdTe 59 , and GaN 60 , demonstrating much superior quality of the 2D layered (PEA) 2 PbI 4 single-crystalline perovskite membrane material.…”
Section: Resultsmentioning
confidence: 65%
“…It is found that the present photosensor shows very high external quantum efficiency (EQE) as much as 26,530%, responsivity ( R ) as high as 98.17 A W −1 , and detectivity ( D *) as large as 1.62 × 10 15 cm Hz 1/2 W −1 (Jones). It should be noted that this detectivity value is not only among the highest detectivity reported to date for all single-crystalline and thin-film perovskite photosensors 56 , it is even higher than devices based on the state-of-the-art material including single-crystalline silicon 56 , InGaAs 57 , GaAs 58 , CdTe 59 , and GaN 60 . Moreover, the flexible membrane photosensor shows excellent mechanical stability.…”
Section: Introductionmentioning
confidence: 78%